ANALISIS PERSEPSI MASYARAKAT KOTA LUBUKLINGGAU TERHADAP PENERAPAN ETLE (Electronic Traffic Law Enforcement) - Rismawanti (Journal Ilmu Sosial, Politik dan Pemerintahan, 2024)
Increased traffic discipline and awareness was realized by the stipulation that the manual ticketing policy was abolished and replaced with an electronic ticketing system. This research aims to analyze the level of perception of the people of Lubuklinggau City regarding the implementation of the Electronic Traffic Law Enforcement system in monitoring traffic conditions in the Lubuklinggau City area. The research was carried out in Lubuklinggau City from October to November 2023, using a survey method. The observation areas are Lubuk Durian sub-district, Jawa Kanan sub-district, Jawa Kiri sub-district, Petanang Ilir sub-district and Simpang Periuk sub-district. Determination of respondents was carried out using a simple random method (Simple Random Sampling). The number of respondents at each research location point was determined based on the percentage of the total population. The respondents taken were adults who use vehicles for daily activities. The number of respondents each taken was 3% of the population in each sub-district. The data obtained was analyzed using SmartPLS software. Based on the research results obtained, several conclusions can be drawn, namely that the level of public discipline in driving in Lubuklinggau City is on average low, while the level of public knowledge and perception regarding the implementation of the ETLE system in Lubuklinggau City is still very low.